Breast cancer drugs perturb fundamental vascular functions of endothelial cells by attenuating protein S‐nitrosylation. (20th October 2019) - Giri, Suvendu; Katakia, Yash Tushar; Chatterjee, Suvro; Gajalakshmi, Palanivel
Abstract: Cardiovascular side effects of broadly used chemotherapeutic drugs such as Tamoxifen citrate (TC), Capecitabine (CP) and Epirubicin (EP) among cancer survivors are well established. Nitric oxide (NO) is known to protect cardiovascular tissues under conditions of stress. NO can act through cyclic guanosine monophosphate (cGMP)‐dependent and ‐independent pathways. Particularly, the S‐nitrosylation of SH‐groups in a protein by NO falls under cGMP‐independent effects of NO. TC, CP, and EP are hypothesized as interfering with cellular protein S‐nitrosylation, which, in turn, may lead to endothelial dysfunctions. The results show that all three drugs attenuate nitrosylated proteins in endothelial cells. A significant reduction in endogenous S‐nitrosylated proteins was revealed by Saville–Griess assay, immunofluorescence and western blot. Incubation with the drugs causes a reduction in endothelial migration, vasodilation and tube formation, while the addition of S‐nitrosoglutathione (GSNO) has a reversal of this effect. In conclusion, results indicate the possibility of decreased cellular nitrosothiols as being one of the reasons for endothelial dysfunctions under TC, CP and EP treatment. Identification of the down‐regulated S‐nitrosylated proteins so as to correlate their implications on fundamental vascular functions could be an interesting phenomenon.